Strategies and instruments for active mobility: the main Italian policies - D’Amico, Annunziata (TeMA - Journal of Land Use, Mobility and Environment, 2024)
Starting from the relationship between urban planning and mobility management, TeMA has gradually expanded the view of the covered topics, always remaining in the groove of rigorous scientific in-depth analysis. This section of the Journal, Review Notes, is the expression of continuously updating emerging topics concerning relationships between urban planning, mobility and environment, through a collection of short scientific papers written by young researchers. The Review Notes are made of four parts. Each section examines a specific aspect of the broader information storage within the main interests of TeMA Journal. In particular, the Urban strategies, programmers and tools section presents the different strategies and tools for active mobility implemented internationally. This work aims to highlight the various actions undertaken at national and local level to promote the spread of active mobility in Italy, providing a general overview of the tools and strategies adopted and also presenting concrete examples of solutions implemented in some cities. The numerous positive experiences at local level allow us to highlight the attention of Italian cities to reduce dependence on the car (and motorcycle) mode in daily travel, in favor of lower-impact modes of transport This trend of promoting active travel (on foot and by bicycle), which is more ecological and healthy, could contribute to achieving the goal of improving the quality of urban environments and the quality of life of people.